A study of the plankton and benthos of Ekole river in Bayelsa state, Nigeria (2007)
A study was undertaken to determine the plankton and benthos of Ekole River in Bayelsa State of Nigeria. Surface water and sediment samples were collected in the dry (December-January) and wet (June –July) seasons between 2003 and 2004 for plankton and benthic analyses. The water temperature ranged from 27-33°C, pH 6.30-7.5, total suspended solids (T.S.S) 110-282 mg/L, Chloride 15.40- 39.6 mg/l, dissolved oxygen 4.11-10.83 mg/l and conductivity 64.5-84.55ìS/cm. The total plankton count ranged between 267 x 10³ and 11830 X 10 ³ / L. Forty three and forty seven species of phytoplankton belonging to five families were identified in the dry and rainy seasons respectively. The mean zooplankton population ranged from 1954 x 10 / L in the dry to 3479 x 10 / L in the wet season while the benthic organisms ranged from 113 x 10 / L to 152 x 10 /L in the rainy and dry seasons respectively. Bacillariophyceae dominated the phytoplankton while the rotifers dominated the zooplankton species. Some biological indicators of pollution: larval forms of Chironomids ,Odonatans and Ephemenopterans were also identified in the river